A Cationic Amphipathic Tilapia Piscidin 4 Peptide-Based Antimicrobial Formulation Promotes Eradication of Bacterial Vaginosis-Associated Bacterial Biofilms - Lin, Wen-Chun; Chen, Yun-Ru; Chuang, Chi-Mu; Chen, Jyh-Yih (Frontiers in Microbiology, 2022)
Bacterial vaginosis (BV) is prevalent among women of reproductive age and has a high rate of recurrence, which can be largely attributed to ineffective BV biofilm eradication by current first-line antibiotics. In this study, we report that the Nile tilapia piscidin 4 (TP4) exhibits broad-spectrum antimicrobial and antibiofilm activity against BV-associated bacteria, but not beneficial lactobacilli. In addition, BV-associated Gardnerella vaginalis remains susceptible to TP4 even after continual exposure to the peptide for up to 22 passages. G. vaginalis and Streptococcus anginosus are both biofilm-forming BV-associated bacteria, and we found that combining TP4 peptide and disodium EDTA with the biofilm-disrupting agent, chitosan, can eradicate biofilms formed by single or mixed G. vaginalis and S. anginosus. In addition, long-term storage of TP4 peptide in chitosan did not diminish its bactericidal activity toward G. vaginalis. Preformulation studies were performed using High performance liquid chromatography (HPLC) and Circular Dichroism (CD). The long-term stability of TP4 peptide was assessed under various conditions, such as different temperatures and ionic strengths, and in the presence of H2O2 and lactic acid. When exposed to sodium dodecyl sulfate (SDS), TP4 maintained its secondary structure at various temperatures, salt and disodium EDTA concentrations. Furthermore, the TP4 microbicide formulation significantly reduced the colonization density of BV-associated bacteria in mice infected with single or mixed bacteria (G. vaginalis and S. anginosus). The TP4 microbicide formulation showed biocompatibility with beneficial human vaginal lactobacilli and female reproductive tissues in C57BL/6 mice. These results suggest that the TP4 microbicide formulation could be a promising topical microbicide agent for BV treatment.